Edukasi Penerapan Bahasa Inggris Untuk Menyatakan Perasaan Dalam Mendukung Mental Health di Islamic Center Binbaz Putri - surip Haryani (LPPM STIKES Madani, 2025)
Mental well-being is also proving to be an extremely serious matter, particularly among teenage girls residing in dormitories. One of the unique ways of assisting with mental well-being is by expressing emotions. As part of the practice of speaking skills in English, the skill of describing emotions—perhaps even in a foreign language—can be used as a vehicle for expressing feelings. This service-learning activity sought to deliver experiential learning in expressing emotion in English to women students from the Islamic Center Binbaz Putri Yogyakarta. The approach employed was participatory training through language games, topic discussions, and role-playing of emotional scenarios. The outcome of the activity was participants' greater comprehension and competence in expressing emotion such as sadness, happiness, anger, disappointment, and fear in English. The activity also promoted further awareness of emotional control being a key aspect of being well in mind. Arguably, the dual approach of linguistic teaching and mental health teaching is a successful method within religious education settings.